Formulasi Ekstrak Propolis dalam Sediaan Sabun Padat - Suharyani, Ine; Rahayu, Nur; Rima Yulia Senja (Medimuh : Jurnal Kesehatan Muhammadiyah, 2025)
Indonesia is one of the countries rich in flora and fauna that are beneficial to humans, one of which is propolis in bees. Pinocembrin, acacetin, chrysin, rutin, catechin are types of flavonoids contained in propolis that are beneficial as antimicrobials, antifungals, and antioxidants. This research aims to formulate propolis extract into solid soap preparations. The research conducted is an experimental study. Data processing in this study was presented in the form of observation tables, including organoleptic observations, pH measurements, foam stability tests, and soap hardness tests. Each test is conducted three times, all averaged and their standard deviations calculated, then analyzed using StatView. The yield of propolis extract through the maceration extraction method with 96% ethanol at a 1:10 ratio as the solvent. The variations in the concentration of propolis extract used are 0.1% (F1); 0.3% (F2); and 0.5%. (F3). The stages of this research include the formulation of soap using palm oil, olive oil, coconut oil, sodium hydroxide, aquades with the addition of oleum rosae as a fragrance. The soap is evaluated in terms of organoleptic properties, pH, foam stability, and hardness. The research results show that the solid soap with propolis extract has a dense consistency with a pale yellowish-white to brownish-white color, and a characteristic rose scent. The produced soap has a pH that is safe for use on the skin, which is 10.61-10.75. This soap also has good foam stability, ranging from 88-95%, and a good soap hardness value of around 5 kg.